Effect of Iron Supplementation on HbA1c levels in Type 1 Diabetic patients - Afshan Nosheen, S. A. Ahmad, Mahrukh Fayyaz, Mahnoor Mohydin, Wali H. Zaidi, M. H. B. A. Malik, S. Mohydin, A. Asghar, Z. Asghar, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate the effect of iron supplementation on HbA1c levels in Anemic type 1 diabetes mellitus individuals and its association. Methodology: A cross-sectional study was conducted on 90 Type 1 Diabetic patients of which 60 had anemia and 30 had normal Hemoglobin levels. Structured questionnaires were used to collect information on socio-demographics and other co-morbidities / clinical conditions. The Cell Dyn 1800 hematological analyzer was used to test the venous blood for a complete blood count (CBC). Alongside, electrochemiluminescence (ECL) E411 (Kit Roche) was used to perform serum ferritin, serum iron, and total iron-binding capacity. HbA1c levels were accessed by glyco-hemoglobin reagent kit. Results: Patient’s hemoglobin levels were 10.1g/dl at baseline and 11.1g/dl following therapy. Anemic patients had an average HbA1c level of 8.603% and after iron supplementation it was 7.608%. On the other hand the HbA1c in the control group was 8.1% previously and after three months was 8.3%. Hence, after three months of therapy, a significant decrease in HbA1c levels was seen. HbA1c levels are altered not only in diabetes but in many other instances including different forms of anemia. This study was aimed at finding the correlation between iron levels and corresponding changes in HbA1c levels. Understanding the role of iron levels on HbA1c values prevents physicians from misevaluating the intensity of diabetes as sometimes a high reading HbA1c may only be due to iron deficiency and not because of increasing severity of diabetes. Conclusion: Anemia has an inverse relationship with HbA1c levels. When the level of hemoglobin lowers in anemic individuals, HbA1c levels rise in tandem. Furthermore, when anemia is corrected, their HbA1c levels drop to near-normal levels. Aside from blood glucose, a variety of additional variables influence the computed HbA1c quantification number, which should be considered before starting or changing a treatment regime. Since iron deficiency anemia is so widespread, it should ideally always be ruled out when high HbA1c levels are identified and addressed promptly, to reach optimal HbA1c values. Key words: Anemia, HbA1c levels, Type 1 Diabetes Mellitus, Hemoglobin (Hb), serum Iron, BSR (Blood Sugar Random)